Prototipe Aplikasi Orang Hilang Berbasis Android Pada Polsek Abepura Kota Jayapura Papua: Prototype of Missing Persons Android-Based Application at Abepura Police Station, Jayapura City, Papua. - Chyntia Mangngiding; Christian Dwi Suhendra; Lion Ferdinand Marini (JISTECH: Journal of Information Science and Technology, 2023)
Data from the Jayapura District Police shows that there was an increase in the number of missing persons in Jayapura City. In January 2022, there were 8 reports of missing persons, and this number doubled to 16 in March 2022. Currently, the police rely on reports from the public to find missing individuals. They then conduct direct checks in the field, confirm the reported characteristics, and contact the families. However, this method is not considered modern or efficient enough to handle the increasing number of missing persons cases. In this modern age, technological developments, especially in mobile applications, can offer more effective and efficient solutions. Therefore, a prototype application for missing persons based on Android was developed as an alternative to help address the issue of missing persons, especially in Jayapura City. The missing persons application underwent black box testing to ensure that its functions and inputs are working correctly, and the validation function was used to check its accuracy. The test results showed that the application is functioning well and can be used as a tool to help find missing persons in the city. However, continuous monitoring and improvement of the application are necessary to ensure that it remains effective in the long term.